2014
DOI: 10.5433/1679-0359.2014v35n3p1267
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da adição de albumina e da temperatura de secagem nas características de polpa de tomate em pó

Abstract: ResumoEste trabalho foi realizado com o objetivo de avaliar a influência da adição de agente espumante e da temperatura de secagem nas características dos pós produzidos a partir de polpa de tomate in natura. Foi avaliada a influência destes tratamentos nas variáveis pH, acidez titulável, ácido ascórbico, densidade compactada, solubilidade e higroscopicidade dos pós produzidos nas temperaturas de secagem de 60ºC e 80 ºC, adicionados ou não de albumina. Verificou-se a ocorrência de maiores valores de acidez e m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
(14 reference statements)
1
8
0
3
Order By: Relevance
“…Fernandes et al (2014) observed that the foam obtained using albumin reduced the time to reach equilibrium moisture in the drying of tomato pulp. Figures 2A and B show the drying curves of the samples containing 4 and 8% of albumin, respectively, fitted to the Midilli model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fernandes et al (2014) observed that the foam obtained using albumin reduced the time to reach equilibrium moisture in the drying of tomato pulp. Figures 2A and B show the drying curves of the samples containing 4 and 8% of albumin, respectively, fitted to the Midilli model.…”
Section: Resultsmentioning
confidence: 99%
“…Fernandes et al (2014), studying the influence of albumin and drying temperature on tomato pulp powder, observed that the time to reach equilibrium moisture decreased by 55% with the increment of temperature from 60 to 80 ºC. In the samples containing 4% of albumin (Figure 2A), the drying times for the samples to reach the moisture ratio of 0.5 were 108.9, 90.8 and 86.5 min at temperatures of 75, 80 and 85 ºC, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to Fernandes et al (2014), 80 °C is the limit temperature for food dehydration, and lower temperatures are tested aiming at preserving nutrients at the end of the process. The samples were weighed until constant weight at regular intervals (30 min).…”
Section: Methodsmentioning
confidence: 99%
“…The longer time for the treatments at 50, 60 and 70 °C may have caused vitamin C exposure to moisture, light and oxygen, contributing to its degradation, which is due to the sensitivity to heat of the ascorbic acid molecule (Fernandes et al, 2014). Ascorbic acid content decreased in the drying of potato (Mehta et al, 2007) and onion (Kadam et al, 2009) subjected to different treatments of temperature.…”
Section: Ementioning
confidence: 99%
See 1 more Smart Citation